Metode Penyelesaian Sengketa dalam Kontrak Asuransi Syariah - Indra Maya Syara (FENOMENA, 2017)
This article analyzes the position of the Religious Court in resolving sharia insurance disputes based on Indonesian Laws that mandates a new authority to the Religious Courts. This article also aims at looking the implementation in the choice of disputes resolution of sharia insurance contracts in Indonesia. Applying an empirical method, this article uses a normative approach without ignoring a sociological perspective. The finding of this article is there are several methods which included in the sharia insurance policy. The first is by in-dept discussions, the second is by involving alternative institution for disputes resolutions like Badan Arbitrase Syariah Nasional (Basyarnas, National Sharia Arbitration Board), Badan Mediasi Asuransi Indonesia (BMAI, Indonesia Insurance Mediation Agency) and so forth. The third, by taking litigation process through Religious Courts or District Courts. This article reveals that the inclusion of District Courts is not relevant to a case of dispute resolution in sharia insurance policy. The irrelevant of District Court in the dispute resolution case because the Courts generally use Indonesian Civil Code and Indonesian Commercial Code which lack of conceptual discussion on sharia economic theories.